Efficient diborane-mediated synthesis of phthalocyanines carrying amino groups near the macrocycle - Gauna, Gabriela Alejandra (2012)
N-(3,4-dicyanophenyl)piperidine-2,6-dione (2) and 4- phthalimidophthalonitrile (3) were synthesized in 24% and 74% yield respectively, using 4-aminophthalonitrile as the starting material. Treatment of 2 and 3 with zinc acetate in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene gave respectively phthalocyanines 4 and 5, whose reduction with diborane afforded dyes 6 and 7. Quaternization of 6 and 7 with iodomethane gave cationic zinc(II) phthalocyanines 8 and 9 respectively. A bathochromic shift was observed in the absorption spectra when amino and ammonium groups were present near the macrocycle in comparison with those dyes carrying alkylamino and quaternary alkyl ammonium salts as peripheral substituents.